General Ordinances of the City of Winchester, Ordinance XXI. Gunpowder. To be kept in metallic canisters in limited quantities (3 March, 1875). - (:unkn) unknown (General Publisher, 1875)
It shall not be lawful for any person or persons or firm, for any purpose whatsoever, to store or keep within the limits of this city a larger quantity of powder than twenty-five pounds. All powder shall be kept well secured in a close tin or other metallic canister ; provided that larger quantities may be kept in such magazine or other place as the council may provide or designate for the storage of powder, subject to such regulations and charges as the council may prescribe.
--
Keywords: GUN POWDER STORAGE